Praktik Sewa Jasa Parafrase Skripsi dalam Perspektif Hukum Islam - Citra Buana Tunggadewi; Yaqin, Ainul (Fakultas Syariah UIN Prof. K.H. Saifuddin Zuhri, 2024)
Currently, there are many types of services, one of which is thesis paraphrasing services, where the thesis with a high percentage of plagiarism will be processed in such a way that the plagiarism rate drops. The purpose of this research is to find out how the practice of renting thesis paraphrasing services in Purwokerto and how Islamic law reviews the practice of renting thesis paraphrasing services. This research is included in the type of field research with juridical-empirical approach. Primary data sources are taken directly from paraphrase service providers in Purwokerto and their service users. The results of this study indicate that the practice of thesis paraphrasing services in Purwokerto is an implementation of the ijarah 'ala al-'amal contract. Regarding the benefits of renting thesis paraphrasing services, it is considered to be in accordance with the provisions of shara' because there is no fraud in it. In this case, the service provider will only change the language order in the thesis. In addition, there is no definite argument or provision from the campus regarding the rules for using thesis paraphrasing services so that this practice is permissible. In terms of service fees (ujrah), some service providers do not determine the clarity of wages or tariffs so that the status of the contract becomes fasid because there is an element of garar.